The FitTrack Index as fitness indicator: A pilot study - Dina Christina Janse van Rensburg; Catharina Cornelia Grant; Audrey Jansen van Rensburg; Roelf Petrus Gerhardus Botha; Paola Silvia Wood; Kim Nolte; Lizelle Fletcher; Peet Jacobus du Toit; Michael Sean Pepper; Pieter Ernst Kruger (AOSIS, 2016)
Background: The FitTrack Index is a web-based programme developed in South Africa and widely used by athletes to indicate their fitness. A need exists for a self-managed, non-invasive tool to evaluate and categorise health-related fitness in different population groups. The aim of this study was to compare the FitTrack Index with a reliable measure of cardio-respiratory fitness as indicated by maximal oxygen uptake (direct VO2max). Methods & results: During a 12-week cross-sectional, descriptive pilot study the direct laboratory tested VO2max indicated a moderate to strong correlation with the FitTrack Index (Spearman's rho = 0.439, p = 0.089 at baseline; Spearman's rho = 0.853, p < 0.001 after 12 weeks). Conclusions: These results suggest that the web-based FitTrack Index may be considered an appropriate tool to evaluate exercise capacity and cardiovascular fitness in healthy individuals following an aerobic training programme.